Experimental human hookworm infection: a narrative historical review. - Paul R Chapman; Paul Giacomin; Alex Loukas; James S McCarthy (PLoS Neglected Tropical Diseases)
In 1896, a serendipitous laboratory accident led to the understanding that hookworms propagate infection by penetrating skin, a theory that was then confirmed with the first experimental human infection, reported in 1901. Experimental human infections undertaken in the 20th century enabled understanding of the natural history of infection and the immune response. More recently, experimental hookworm infection has been performed to investigate the immunomodulatory potential of hookworm infection and for the evaluation of hookworm vaccines and chemotherapeutic interventions. Experimental human hookworm infection has been proven to be safe, with no deaths observed in over 500 participants (although early reports predate systematic adverse event reporting) and no serious adverse events described in over 200 participants enrolled in contemporary clinical trials. While experimental human hookworm infection holds significant promise, as both a challenge model for testing anti-hookworm therapies and for treating various diseases of modernity, there are many challenges that present. These challenges include preparation and storage of larvae, which has not significantly changed since Harada and Mori first described their coproculture method in 1955. In vitro methods of hookworm larval culture, storage, and the development of meaningful potency or release assays are required. Surrogate markers of intestinal infection intensity are required because faecal egg counts or hookworm faecal DNA intensity lack the fidelity required for exploration of hookworm infection as a vaccine/drug testing platform or as a regulated therapy.